2022
DOI: 10.1186/s13148-022-01374-9
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age acceleration is associated with epigenetic biomarkers of prenatal physiologic stress exposure

Abstract: Background Physiological maternal stress response, such as imbalance in the glucocorticoid pathway and immune system seems to be mediated by DNA methylation (DNAm) and might translate intrauterine stress exposures into phenotypic changes in a sex-specific manner. DNAm in specific sites can also predict newborn gestational age and gestational age acceleration (GAA). GAA occurs when the predicted biological age is higher than the chronological age. In adults, poor health outcomes related to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Overall, our ndings do not support a link between prenatal stress exposure and gestational epigenetic age (or age acceleration/deceleration) at birth in the general paediatric population. These ndings differ from previously published studies reporting a link between prenatal stress and either gestational epigenetic age deceleration 26,25,19 or acceleration [27] [21] [52]. Several factors may explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Overall, our ndings do not support a link between prenatal stress exposure and gestational epigenetic age (or age acceleration/deceleration) at birth in the general paediatric population. These ndings differ from previously published studies reporting a link between prenatal stress and either gestational epigenetic age deceleration 26,25,19 or acceleration [27] [21] [52]. Several factors may explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, a study in Brazil in 83 newborns found an association between gestational epigenetic age acceleration and maternal negative feelings related to pregnancy, though this was not associated with any other psychosocial variables. They further found that gestational epigenetic age acceleration could be predicted by epigenetic scores of low-grade in ammation and glucocorticoid exposure [27]. A study in the Democratic Republic of Congo, on 141 newborns, also found that those prenatally exposed to general trauma and war trauma displayed epigenetic age acceleration at birth.…”
Section: Introductionmentioning
confidence: 92%
“…The fetal hypothalamic-pituitary-adrenal (HPA) axis is especially susceptible to glucocorticoids long-term programming, and these effects can persist throughout life (Moisiadis & Matthews, 2014). A previous study in Brazil found accelerated gestational epigenetic age in infants exposed to glucocorticoids and low-grade inflammation indices (Euclydes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Since LES only measures recent stressful and traumatic events, whereas STRESS assesses lifetime events and associated PTSD symptoms, we can speculate that cumulative exposure and trauma-specific symptoms might be necessary for reliable epigenetic changes to occur. In addition, PTSD usually co-occurs with immune dysregulation [ 67 ], which might influence gestational epigenetic age acceleration [ 68 ].…”
Section: Discussionmentioning
confidence: 99%